(untitled) - Wilbur, Richard ([New York], 2003)
This compilation includes previously unreleased archival readings of his early work, plus newly recorded versions of more recent poems--all of them in Wilbur's own resonant voice.
Keywords: American poetry,Thơ Mỹ